2022
DOI: 10.3390/ijms231911317
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Resistance in Vascular Disease: A Review Highlighting the Critical Need for Improved Point-of-Care Testing and Personalized Therapy

Abstract: Aspirin resistance describes a phenomenon where patients receiving aspirin therapy do not respond favorably to treatment, and is categorized by continued incidence of adverse cardiovascular events and/or the lack of reduced platelet reactivity. Studies demonstrate that one in four patients with vascular disease are resistant to aspirin therapy, placing them at an almost four-fold increased risk of major adverse limb and adverse cardiovascular events. Despite the increased cardiovascular risk incurred by aspiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 113 publications
0
4
0
Order By: Relevance
“…Blood samples from patients were analysed two weeks after commencement of treatment using thromboelastography (TEG®) 16,28 and the PFA200 platelet function analyser 29 . These analyses were done to ensure that a hypocoagulable state putting the patient at risk of bleeding had not been induced 30 , and to rule out clopidogrel and/or aspirin resistance 31,32,33,34…”
Section: Anticoagulant Treatment Regimenmentioning
confidence: 99%
“…Blood samples from patients were analysed two weeks after commencement of treatment using thromboelastography (TEG®) 16,28 and the PFA200 platelet function analyser 29 . These analyses were done to ensure that a hypocoagulable state putting the patient at risk of bleeding had not been induced 30 , and to rule out clopidogrel and/or aspirin resistance 31,32,33,34…”
Section: Anticoagulant Treatment Regimenmentioning
confidence: 99%
“…For example, based on the existing literature, the incidence of aspirin resistance in the population ranges from 0.4% to 83.3%. 4 The exact mechanism of antiplatelet drug resistance has not been fully elucidated. Studies have shown that gene polymorphism is one of the factors affecting antiplatelet drug resistance and this will be discussed further in this narrative review.…”
Section: Introductionmentioning
confidence: 99%
“…Although other anti-platelet drugs, such as clopidogrel, have shown almost the same activity, acetylsalicylic acid is still one of the treatment therapies for the population of patients with this disease. The relatively low cost and ease of acquisition in healthcare are the primary reasons for the predominant use of acetylsalicylic acid over other antiplatelet drugs [11,12,13].…”
Section: Introductionmentioning
confidence: 99%